Significant Increase of Cinnamic Acid in Metabolites of Chicks Infected with Infectious Bronchitis Virus and Its Remarkable Antiviral Effects In Vitro and In Vivo - Lan-Ping Wei; Tao-Ni Zhang; Yu Zhang; Li-Na Ren; Yan-Peng Lu; Tian-Chao Wei; Teng Huang; Jian-Ni Huang; Mei-Lan Mo (Microorganisms)
Avian infectious bronchitis virus (IBV) infection has caused significant economic losses to the poultry industry. Unfortunately, there is currently no effective cure for this disease. Understanding the pathogenic mechanism is crucial for the treatment of the disease. Studying the pathogenic mechanism of IBV based on metabolomics analysis is helpful for identifying antiviral drugs. However, studies on metabolomics analysis of IBV infection have been relatively limited, particularly without metabolomics analysis in sera after IBV infection. In this study, 17-day-old SPF chicks were infected with the IBV GX-YL5 strain, and serum samples were collected 7 days post-infection (DPI) for metabolomics analysis using ultraperformance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). A total of 143 differential metabolites were identified across 20 metabolic pathways, with the phenylalanine pathway showing the most significant changes. The level of cinnamic acid (CA), an upstream metabolite in the phenylalanine pathway, was notably increased following IBV infection. To investigate the antiviral effects of CA, chicken embryo kidney (CEK) cells and SPF chicks infected with IBV were treated with different concentrations of CA to assess its effect on viral replication. The results demonstrated that CA at 25 μg/mL effectively inhibited IBV replication in vitro; meanwhile, CA at 50 μg/mL and 25 μg/mL effectively inhibited IBV replication in vivo. Molecular docking and molecular dynamics simulation studies showed that CA interacts with the N domains of the IBV nucleocapsid (N) protein. In conclusion, the serum metabolite CA is significantly elevated following IBV infection and demonstrates remarkable antiviral effects both in vitro and in vivo, providing a promising avenue for the development of antiviral therapies to combat IBV infection.